Irregular shapes of water clusters generated in supersonic expansions - Lengyel, J; Pysanenko, A; Poterya, V; Slavíček, P; Fárník, M; Kočišek, J; Fedor, J (Physical review letters, 2014)
We report cross sections for pickup of guest molecules on neutral argon and water clusters with the mean sizes in the range from N = 50 to 600. The experiments are supported by molecular dynamics simulations and analytical models based on the interaction potentials. The cross sections for argon clusters are consistent with their assumed spherical shape and follow approximately the theoretically justified N(1/3) dependence. On the other hand, the cross sections of water clusters depart from this dependence and are considerably larger starting from N ≥ 300. We interpret this increase of cross section by the occurrence of highly irregular shapes of water clusters produced in the supersonic expansion of water vapor under the conditions of the large cluster generation.
Keywords: Thermodynamics; Molecular Dynamics Simulation; voda; chemické modely; Models, Chemical; velikost částic; Argon; Water; simulace molekulární dynamiky; termodynamika; argon; Particle Size